Factors that Facilitate and Hinder the Comprehension of Patient Information Leaflets (PILs): A Brief Scoping Review - Medina-Córdoba, Mariana; Cadavid, Sara; Pérez-Acosta, Andrés M.; Amaya-Giraldo, Valentina (Frontiers in Pharmacology, 2021)
Introduction: Patient information leaflets (PILs) of medicinal products are informative documents that accompany medicines and explain their components, modes of use, interactions with other medicines, and other relevant issues. When patients do not adequately understand the information in the leaflets, they may engage in behaviors that affect their health (e.g., self-medication). Objective: To identify patient-related factors and characteristics of PILs that can promote cognitive, emotional, and behavioral change that leads to appropriate drug use practices. Additionally, we aimed to determine strategies that could be implemented to design leaflets that convey adequate information and are easier to understand. Issues addressed: We evaluated scientific articles published in databases and containing information on PILs suitability to be used in a patient population. A total of 51 articles were selected as the sample. Certain leaflet factors that favored or hindered understanding were identified (e.g., format in which the leaflets are presented, their structure, their adaptation to the sociodemographic and linguistic characteristics of the population, their wording…). Similarly, we also identified patient factors, such as previous experience taking the drugs referred to in the leaflet; the type of emotions experienced when reading the leaflets; the emphasis on the adverse effects of the medications; sociodemographic variables (i.e., age or educational level); and degree of interest in their own healthcare. Conclusions: Patient and leaflet factors influence the comprehension of information in the PIL; hence, emphasis should be placed on these factors to increase treatment and medication adherence and to reduce health-risk behaviors.